MODEL PERTUMBUHAN EKONOMI MANKIW ROMER WEIL DENGAN PENGARUH PERAN PEMERINTAH TERHADAP PENDAPATAN - Desi Oktaviani (Jurnal Matematika, 2016)
ABSTRACT. Mankiw Romer Weil model is one of economic growth model. In this paper, we will present a Mankiw Romer Weil economic growth model development with role of government influence on income. Furthermore, invesment on human capital and physic capital expenditure is from net income and no longer using gross income. Net income represents the amount of money remaining after all operating expenses have been deducted from gross income by government.  A three sector closed economy model is constructed by adding government sector to the two sector closed economy which consist of household and business sector and there is no international trade. Analysis of steady state in Mankiw Romer Weil economic growth model with role of government influence can be obtained one equilibrium point for human and physic capital per effective labor. Then,this model are analyzed to determine the stability of the equilibrium point. The stability of the equilibrium point criteria is based on eigenvalues from Jacobian matrix and we show that eigenvalues of Jacobian matrix are real, distinct and negative so the equilibrium point is asymptotically stable. Keywords :